Ontology: Unreal Reality - Piotr Jaroszyński (Studia Gilsoniana, 2014)
The article examines the difference between ontology and metaphysics. It shows that as soon as the composition of being from essence and existence is treated as purely mental or in a “reified” way (where essence and existence are independent elements), then essence as essence becomes a thing, and then simply becomes a being, or what is called reality. Both versions in which the real difference disappears or in which the road leads to “reification,” influence the treatment of essence as independent, where essence as thing fills the field of reality. However, if essence was only possibility, then (1) the reality also would be merely possible, (2) the realistic field of philosophical terminology would get curtailed, and (3) there would be no terms to maintain the difference between reality and possibility, between metaphysics and ontology.